PENDAMPINGAN KETERAMPILAN MENULIS STRORYLINE KEPADA POKDARWIS UNTUK PENGUATAN GEOWISATA DI BATUKLIANG UTARA - Sri Sukarni; Wulandari, Yayang Erry (LPPM Institut Pendidikan Nusantara Global, 2024)
Human resources are needed to further improve and develop skills that support their professions through various training activities. Likewise, the Tourism Awareness Group (Pokdarwis) need to improve their knowledge in skills in writing because Pokdarwis have a very important role in developing tourism in village through interpretive tourist guide. In general, this Community Service activity aims to develop Pokdarwis knowledge to complete storyline according to the theme and outline of the advantages of tourist attractions. The method of implementing this Community service activity is divided into three stages, namely preparation, implementation and evaluation. Based on the results and discussions, it can be concluded that:1) Pokdarwis have the knowledge and ability to complete a storyline according to the theme and outline that are in accordance with the advantages and geotourism attractions; 2) Pokdarwis have the basic knowledge and ability to prepare the application of personal interpretation techniques that can be used in developing interpretations on the Geotourism routes of North Batukliang Tourism village; 3) Geopark Rinjani Lombok has a guide for interpretive tour guides of the geotourism routes in four North Batukliang villages.